Inorganic solid electrolyte ceramic material containing oxygen vacancies and preparation method thereof

The two-step reduction method forms oxygen vacancy in the garnet solid electrolyte LLZO, which solves the problem of insufficient performance of the existing LLZO electrolyte and significantly improves its ionic conductivity and density.

CN119462149APending Publication Date: 2025-02-18JIANGSU JIUWU HITECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411612387.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing garnet solid electrolyte LLZO has problems such as large grain boundary resistance, low discharge specific capacity, and poor rate performance, and it is difficult to successfully create oxygen vacancy at low sintering temperatures.

Method used

The inorganic solid electrolyte ceramic material containing oxygen vacancy was prepared by a two-step reduction method. The LLZTO fine powder was first reduced at a high temperature under a reducing atmosphere, and then the tablet was secondary to form an oxygen vacancy, reducing the activation energy of lithium ions transported, and improving the Ion conductivity.

Benefits of technology

The ionic conductivity and density of solid electrolytes are improved, and the oxygen vacancy defect reduces the activation energy of lithium ions to transport and improves the migration rate of lithium ions, and the conductivity reaches 7.13×10−4S/cm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005131244200000011
    Figure HDA0005131244200000011
  • Figure HDA0005131244200000012
    Figure HDA0005131244200000012
  • Figure HDA0005131244200000013
    Figure HDA0005131244200000013
Patent Text Reader

Abstract

The invention discloses an inorganic solid electrolyte ceramic material containing oxygen vacancies and a preparation method thereof, and belongs to the technical field of lithium ion batteries. Tantalum-doped lithium lanthanum zirconate (LLZTO) solid electrolyte powder with a garnet type cubic phase structure is prepared through a solid phase method, the LLZTO fine powder obtained through grinding is subjected to annealing treatment in a reducing atmosphere to obtain LLZTO fine powder containing oxygen vacancies, the powder is subjected to cold press molding after being subjected to ball milling and drying, and the electrolyte sheet containing the oxygen vacancies is obtained through high-temperature sintering in the reducing atmosphere. According to the present invention, the Ta-doped LLZO is synthesized, the lattice of the prepared solid electrolyte contains the oxygen vacancy through the two-time reduction, the oxygen vacancy defect can reduce the activation energy of the lithium ion transmitted along the crystal grain and the crystal boundary, and the rapid migration of the lithium ion on the surface of the electrolyte is promoted so as to improve the ionic conductivity of the electrolyte sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to an inorganic solid electrolyte ceramic material containing oxygen vacancies and a preparation method thereof. Background Art

[0003] Lithium-ion batteries have become the most widely used energy storage device and the preferred power source for electric vehicles due to their high energy density, no memory effect, and long service life. Traditional rechargeable batteries often use liquid electrolytes to separate the positive and negative electrodes, but liquid electrolytes are flammable during thermal runaway, emit gas at high voltages, and are chemically incompatible with lithium metal negative electrodes. Specifically, when Li metal is used as the negative electrode of a lithium battery in combination with a liquid electrolyte, problems such as excessive growth of lithium dendrites piercing the diaphragm, causing a short circuit in the battery, and continuous reaction between lithium metal and the electrolyte will occur. As an alternative, solid electrolytes have been proposed for the next generation of rechargeable batteries.

[0004] Compared with liquid electrolytes, solid electrolytes tend to reduce the total weight and volume of the battery, thereby increasing its mass energy density and volume energy density. In addition, solid electrolytes have high mechanical strength that can inhibit the penetration of lithium dendrites, are stable to Li metal, and are non-flammable, making it possible for Li metal to be used as the negative electrode. As an important component of solid-state batteries, the performance of solid electrolytes plays a vital role in the electrochemical performance of batteries. The introduction of oxygen vacancies in solid electrolytes can reduce the activation energy of Li ion transmission in solid electrolyte grains and grain boundaries, promote the rapid migration of Li ions on their surface, and improve the ionic conductivity of the electrolyte.

[0005] At present, the solid electrolytes that can be used mainly include oxides, sulfides, polymers, etc. Among them, garnet-type solid electrolytes have the advantages of high temperature resistance, stable chemical properties, wide electrochemical window, and high lithium ion conductivity. They are the mainstream products of oxide solid electrolytes.

[0006] Lithium lanthanum zirconium oxide (LLZO) is the most studied garnet-type solid electrolyte, which has the advantages of high ionic conductivity at room temperature, wide electrochemical window, and stable chemical properties to metallic lithium anode. Chinese patent CN 109950616 A discloses an oxygen vacancy solid electrolyte Li 7-2x La 3 Zr 2 O 12-x, which effectively improves the ionic conductivity of solid electrolytes by generating oxygen vacancies through high-temperature sintering of LLZO, but LLZO still has problems such as large grain boundary resistance, low discharge specific capacity, and poor rate performance. In order to further improve the density and ionic conductivity of garnet-type LLZO solid electrolytes, doping and modification may be a feasible strategy, because doping elements can replace cations Li, La or Zr to stabilize the cubic and tetragonal phases.

[0007] Jeffrey W. Fergus's group at Auburn University selected Ta as the doping element and synthesized Ta-doped LLZO (LLZTO) at a low sintering temperature of 1100 °C by coprecipitation. The study pointed out that by adding LiOH to the covering powder, the evaporation of LLZTO particles during sintering can be minimized, and the relative density reaches 92%, and the total Li conductivity is 6.9×10 −4 However, this method of preparing solid electrolytes by coprecipitation may cause excessive local concentration, agglomeration or uneven composition because a precipitant needs to be added during the preparation process. Although additives were used in this study to obtain high density, oxygen vacancies were not successfully created.

[0008] In summary, if the process can be improved to achieve both Ta doping of LLZO and successful creation of oxygen vacancies, it will undoubtedly help to further improve the ionic conductivity of the solid electrolyte, but no related reports have been seen in the prior art. Summary of the invention

[0009] The purpose of the present invention is to solve the problems existing in the prior art and provide an inorganic solid electrolyte ceramic material containing oxygen vacancies and a preparation method thereof. Oxygen vacancies are generated by two-step reduction to reduce the activation energy of lithium ion transmission in tantalum-doped solid electrolyte materials, increase the migration rate of lithium ions, and thus achieve the effect of improving the ionic conductivity of the solid electrolyte.

[0010] In order to achieve the above technical objectives, the present invention is implemented by the following technical scheme: a method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies, comprising the following steps: 1) For the precursor material Li 2 CO 3 、ZrO 2 、 2 O 5 ,La 2 O 3 Pre-calcining; 2) Weighing the precursor material and performing wet ball milling, and drying after the ball milling to obtain a mixed precursor; 3) The mixed precursor is calcined at high temperature by a solid phase reaction method to obtain a tantalum-doped solid electrolyte powder, which is referred to as LLZTO powder; 4) Wet ball milling is performed on the LLZTO powder, and after the ball milling is completed, the LLZTO powder is dried to obtain LLZTO fine powder; 5) High-temperature reduction of LLZTO fine powder under reducing atmosphere; 6) The LLZTO fine powder after the primary reduction treatment is tableted at a pressure of 180-300 MPa; 7) The LLZTO pressed sheet is subjected to high-temperature reduction in a reducing atmosphere to obtain an inorganic solid electrolyte ceramic material containing oxygen vacancies.

[0011] Furthermore, in step 1), La 2 O 3 The precalcination process of Li 2 CO 3 、ZrO 2 、 2 O 5 The pre-calcination process is carried out separately; To La 2 O 3 The pre-calcination temperature is 900-1000°C, the atmosphere is air, and the calcination time is 12-15 h. Since lanthanum oxide easily absorbs moisture in the air to generate lanthanum hydroxide, the pre-calcination is mainly to dehydrate the denatured lanthanum hydroxide to regenerate lanthanum oxide.

[0012] Opposite 2 CO 3 、ZrO 2 、 2 O 5 The pre-calcination temperature is 200~400℃, the atmosphere is air, and the calcination time is 3~6 h. 2 CO 3 、ZrO 2 、 2 O 5 Pre-calcination is mainly performed to remove impurities such as moisture and carbon dioxide in the precursor material.

[0013] Furthermore, in step 2), the precursor material Li 2 CO 3 ,La 2 O 3 、ZrO 2 、 2 O 5 The molar ratio is 2~5:1~3:1~2:0.2~0.8.

[0014] Furthermore, in step 2), grinding balls and isopropanol solvent need to be added to the precursor material during wet ball milling, the mass ratio of the precursor material, grinding balls and isopropanol solvent is 1:3:5, the ball milling speed is 200-300 rpm, the ball milling time is 6-12 h; and the drying temperature is 80-90°C.

[0015] Furthermore, in step 3), the solid phase reaction temperature is 900-1000°C, the heating rate is 2-5°C / min, the insulation time is 6-10 h, and the furnace is cooled after the insulation is completed.

[0016] Furthermore, in step 4), grinding balls and isopropanol solvent need to be added to the LLZTO powder during wet ball milling, the mass ratio of LLZTO powder, grinding balls and isopropanol solvent is 1:4:7, the ball milling speed is 300-500 rpm, and the ball milling time is 8-16 h.

[0017] Furthermore, in step 5), the reducing atmosphere is argon, nitrogen, H 2 / N 2 Mixed gas or H 2 / Ar mixed gas, the reduction temperature is 900~1000℃, and the reduction time is 10~30 h.

[0018] Furthermore, in step 7), the reducing atmosphere is argon, nitrogen, H 2 / N 2 Mixed gas or H 2 / Ar mixed gas, the reduction temperature is 1100~1300℃, and the reduction time is 10~48 h.

[0019] Preferably, in steps 5) and 7), the reducing atmosphere is 20% H 2 / Ar mixed gas.

[0020] The inorganic solid electrolyte ceramic material containing oxygen vacancies prepared by the above method has a chemical formula of Li 7-σ La 3 Zr x Ta 2-x O 12 , where 0<x≤1.2, 0<σ≤0.5. This electrolyte material can be further applied in lithium-ion batteries, micro-power sources and devices, electrochromic devices and other electrochemical processes.

[0021] The beneficial effects of the present invention are: 1. The electrolyte material prepared by the method disclosed in the present application is a tantalum-doped lithium lanthanum zirconium oxide (LLZO) solid electrolyte sheet. The present application not only achieves the effect of tantalum doping to stabilize the cubic phase and improve the material density, but also makes the prepared solid electrolyte lattice contain oxygen vacancies through secondary reduction. The presence of oxygen vacancy defects can reduce the activation energy required for lithium ion transmission and increase the lithium ion migration rate, ultimately achieving the purpose of improving the conductivity of the solid electrolyte; 2. This application uses a two-step reduction method to prepare a solid electrolyte, and the reducing atmosphere is H 2 / Ar 2 Mixed gas, along with H 2 With the increase of concentration, the ionic conductivity of the electrolyte is improved more and more obviously. When the reducing atmosphere is 20% H 2 / Ar mixed gas, the ionic conductivity of the electrolyte sheet can reach 7.13×10 -4 S / cm. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is an X-ray diffraction (XRD) diagram of the final product obtained before reduction and after two reductions of the LLZTO fine powder in Example 1; Figure 2 The middle panel a is a scanning electron microscope (SEM) image of the cross section of the LLZTO solid electrolyte ceramic material containing oxygen vacancies prepared in Example 1, and the middle panel b is an element distribution (mapping) image of La, Zr, Ta, and O; Figure 3 This is an electrochemical impedance spectroscopy (EIS) graph of the LLZTO solid electrolyte ceramic material containing oxygen vacancies prepared in Example 1; Figure 4 This is the Arrhenius plot of the LLZTO solid electrolyte ceramic material containing oxygen vacancies prepared in Example 1; Figure 5 The ionic conductivity and conductivity activation energy data statistics of the final products prepared in Examples 1-4 and Comparative Example 1 are shown in FIG. DETAILED DESCRIPTION

[0023] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention. Example

[0024] This embodiment discloses a method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies: 1) Using muffle furnace to 2 CO 3 、ZrO 2 、2 O 5 The pre-calcination was carried out in an air atmosphere at a temperature of 300 °C and a calcination time of 4 h.

[0025] 2) Using muffle furnace to measure La 2 O 3 The pre-calcination is carried out in an air atmosphere at a temperature of 900° C. and a calcination time of 12 hours. The pre-calcination can dehydrate the lanthanum hydroxide generated by lanthanum oxide when it is exposed to moisture in the air and regenerate lanthanum oxide.

[0026] 3) Weigh the pre-calcined precursor material Li according to the molar ratio of 3.68:1.5:1.4:0.6 2 CO 3 ,La 2 O 3 、ZrO 2 and Ta 2 O 5 Among them, the weighed amount of lithium source needs to exceed the calculated theoretical content by 15%. This treatment is helpful to compensate for the lithium loss during subsequent sintering.

[0027] 4) Place the precursor material weighed in the previous step into a planetary ball mill, add grinding zirconium balls and isopropanol solvent for ball milling mixing, the mass ratio of precursor material, grinding balls and isopropanol solvent is 1:3:5, the ball milling speed is 200-300 rpm, and the ball milling time is 10 h. After the ball milling is completed, the ball milled mixture is dried by rotary evaporation at 90°C to obtain a mixed precursor powder.

[0028] 5) The mixed precursor powder is placed in a high-temperature furnace and calcined in an air atmosphere at a calcination temperature of 950°C, a heating rate of 5°C / min, and a holding time of 8 h. The mixture is cooled to room temperature to obtain a tantalum-doped solid electrolyte powder, which is recorded as LLZTO powder.

[0029] 6) Put the LLZTO powder into a planetary ball mill, add grinding zirconium balls and isopropanol solvent for ball milling and mixing, the mass ratio of LLZTO powder, grinding balls and isopropanol is 1:4:7, the ball milling speed is 400 rpm, the ball milling time is 10 h, and after the ball milling is completed, the LLZTO fine powder is obtained by rotary evaporation and drying.

[0030] 7) The LLZTO fine powder prepared in the previous step was subjected to high-temperature reduction treatment in a tubular furnace under a reducing atmosphere with a 5% H 2 / Ar 2 Mixed gas, reduction temperature is 1000℃, time is 12 h.

[0031] 8) The LLZTO fine powder after the primary reduction treatment is placed in a mold for uniaxial tableting at a pressure of 220 MPa to obtain LLZTO sheets.

[0032] 9) The LLZTO sheet was subjected to high temperature reduction treatment in a tubular furnace under a reducing atmosphere with a 5% H 2 / Ar 2 The mixed gas was reduced at a temperature of 1200 °C for 15 h to obtain LLZTO solid electrolyte ceramic material containing oxygen vacancies. Example

[0033] The only difference between this embodiment and embodiment 1 is that the reducing atmosphere in steps 7) and 9) is adjusted to 10% H 2 / Ar 2 Mixed gas, the rest of the steps and processes are the same. Example

[0034] The only difference between this embodiment and embodiment 1 is that the reducing atmosphere in steps 7) and 9) is adjusted to 15% H 2 / Ar 2 Mixed gas, the rest of the steps and processes are the same. Example

[0035] The difference between this embodiment and embodiment 1 is that the reducing atmosphere in steps 7) and 9) is adjusted to 20% H 2 / Ar 2 Mixed gas, the rest of the steps and processes are the same.

[0036] Comparative Example 1 The difference between this embodiment and embodiment 1 is that step 7) is eliminated and the sintering atmosphere in step 9) is changed to air.

[0037] Related performance tests: 1. Figure 1 Figure 1 is the X-ray diffraction (XRD) diagram of the final product of LLZTO fine powder before reduction and after two reductions in Example 1. It can be seen from the figure that after heat treatment in reducing atmosphere, the diffraction peak position of LLZTO shifts to the right as a whole compared with that before reduction. This can be explained by the precipitation of oxygen in the powder to produce oxygen vacancies, resulting in a decrease in the unit cell parameters and an increase in the interplanar spacing. d According to Bragg's law, the interplanar spacing d When the diffraction angle is reduced, to satisfy the equation, θ It must be increased, and the corresponding diffraction peak shifts to the right as a whole.

[0038] Figure 2 The cross-sectional morphology of the LLZTO solid electrolyte ceramic material containing oxygen vacancies prepared in Example 1 is presented. It can be seen that the material has a higher density and fewer voids; the mapping diagram shows that the distribution of different elements is relatively uniform.

[0039] Figure 3 The electrochemical impedance diagram of the LLZTO solid electrolyte ceramic material containing oxygen vacancies prepared in Example 1 shows that the ionic conductivity of this material is 5.73×10 -4 S / cm, grain resistance and grain boundary resistance are 55 and 150Ω respectively.

[0040] Figure 4 This is the Arrhenius plot of the LLZTO solid electrolyte ceramic material containing oxygen vacancies prepared in Example 1. It is calculated that the conductivity activation energy of the material is 0.30 eV.

[0041] Figure 5 When H 2 / Ar 2 Reducing H in mixed gas 2 The influence of different concentrations on the ionic conductivity and conductivity activation energy of the electrolyte sheet. Reducing the electrolyte to obtain oxygen vacancies can improve its ionic conductivity and reduce the conductivity activation energy. It can be seen from the figure that H 2 / Ar 2 Reducing H in mixed gas 2 The higher the concentration, the greater the effect on improving material performance. When the reducing atmosphere is 20% H 2 / Ar 2 When mixed with gas, the ion potential of the material is 0.25 eV and the ion conductivity can reach 7.13×10 -4 S / cm, the performance is significantly improved.

[0042] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.

Claims

1. A method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies, characterized in that: The steps include: 1) Pre-calcining the precursor materials Li2CO3, ZrO2, Ta2O5 and La2O3; 2) Weigh the precursor material and perform wet ball milling. After the ball milling is completed, dry it to obtain a mixed precursor; 3) The mixed precursor is calcined at high temperature by a solid phase reaction method to obtain a tantalum-doped solid electrolyte powder, which is referred to as LLZTO powder; 4) Wet ball milling is performed on the LLZTO powder, and after the ball milling is completed, the LLZTO powder is dried to obtain LLZTO fine powder; 5) High-temperature reduction of LLZTO fine powder under reducing atmosphere; 6) tabletting the LLZTO fine powder after the primary reduction treatment; 7) The LLZTO pressed sheet is subjected to high-temperature reduction in a reducing atmosphere to obtain an inorganic solid electrolyte ceramic material containing oxygen vacancies.

2. The method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies according to claim 1, characterized in that: In step 1), the pre-calcination process of La2O3 is carried out separately from the pre-calcination process of Li2CO3, ZrO2 and Ta2O5; the temperature for pre-calcination of La2O3 is 900~1000℃, the atmosphere is air, and the calcination time is 12~15 h; the temperature for pre-calcination of Li2CO3, ZrO2 and Ta2O5 is 200~400℃, the atmosphere is air, and the calcination time is 3~6 h.

3. The method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies according to claim 1, characterized in that: In step 2), the molar ratio of the precursor materials Li2CO3, La2O3, ZrO2, and Ta2O5 is 2~5:1~3:1~2:0.2~0.8; when wet ball milling is performed, grinding balls and isopropanol solvent are added to the precursor materials, the mass ratio of the precursor materials, grinding balls, and isopropanol solvent is 1:3:5, the ball milling speed is 200~300 rpm, and the ball milling time is 6~12 h; the drying temperature is 80~90°C.

4. The method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies according to claim 1, characterized in that: In step 3), the solid phase reaction temperature is 900-1000°C, the heating rate is 2-5°C / min, the holding time is 6-10 h, and the furnace is cooled after the holding is completed.

5. The method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies according to claim 1, characterized in that: In step 4), grinding balls and isopropanol solvent need to be added to the LLZTO powder during wet ball milling. The mass ratio of LLZTO powder, grinding balls and isopropanol solvent is 1:4:

7. The ball milling speed is 300-500 rpm and the ball milling time is 8-16 h.

6. The method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies according to claim 1, characterized in that: In step 5), the reducing atmosphere is argon, nitrogen, H2 / N2 mixed gas or H2 / Ar mixed gas, the reducing temperature is 900-1000°C, and the reducing time is 10-30 h.

7. The method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies according to claim 6, characterized in that: In step 7), the reducing atmosphere is argon, nitrogen, H2 / N2 mixed gas or H2 / Ar mixed gas, the reducing temperature is 1100~1300°C, and the reducing time is 10~48 h.

8. The method for preparing an inorganic solid electrolyte ceramic material containing oxygen vacancies according to claim 7, characterized in that: In steps 5) and 7), the reducing atmosphere is a 20% H2 / Ar mixed gas.

9. An inorganic solid electrolyte ceramic material containing oxygen vacancies, characterized in that: It is prepared based on the preparation method described in any one of claims 1 to 9, and the material chemical formula is Li 7-σ LqCy x Ta 2-x O 12 , where 0<x≤1.2, 0<σ≤0.

5.

10. Use of the inorganic solid electrolyte ceramic material containing oxygen vacancies as claimed in claim 9 in a lithium ion battery.

Citation Information

Patent Citations

  • Method for improving conductivity of oxide solid electrolyte

    CN109687019A

  • Oxygen vacancy solid electrolyte, cathode material, positive plate, lithium ion battery and preparation technology

    CN109950616A

  • Solid electrolyte, preparation method thereof and solid-state battery

    CN111943263A

  • Preparation method of solid electrolyte

    CN117393844A

  • Solid electrolyte and fabrication method therefor, and all-solid-state secondary battery and fabrication method therefor

    US20170162903A1